Effect of perceptual-motor training on dynamic balance of 11 to 14 years old mental retarded boys Abstract - Mokhtar Salari-Askar; Mahshid Zarezadeh; Mohammadtaghi Amiri-Khorasani (Vesnu Publications, 2014)
Introduction: Attention to postural control in individuals with intellectual disability is an important issue because of lower balance performance in this group. The aim of present study was to evaluate the effects of perceptual-motor training on dynamic balance of students with intellectual disability. Materials and Methods: The present study is quasi experimental. Thirty students with intellectual disability (IQ between 55 and 70) and mean age of 12.4±1.7 years (range 11 to 14 years) with Available sampling were recruited to participate in this study and they placed in experimental and control group randomly. Before and after perceptual-motor training, dynamic balance was measured with Biodex system. Training program included three sessions per week (each session 45 min) for 12 weeks. Perceptual motor components including; static and dynamic balance, identified different ways, identify the body, perception space, coordinated and simultaneous movements, visual perception, auditory perception, motion design, superior lateral, handling skills and manipulation. Paired sample t test and one-way Analysis of Covariance (ANCOVA), with significance levels of 0.05, was performed respectively to assess differences between pre&post test and differences between groups. Results: Results of this study showed that significantly lower anterior-posterior balance index (P=0.003) and total balance index (P= 0.017) during post test in experimental group in compared to control group, while Medio-lateral balance index didn't show any significant differences between groups (P=0.155). Conclusion: Perceptual-motor training used in this study improves dynamic balance, especially in anterior-posterior direction in individuals with intellectual disability. Keywords: Perceptual-motor training, dynamic balance, intellectual disability